ANALISIS TREN PERUBAHAN SUHU UDARA DAN CURAH HUJAN BERDASARKAN DATA OBSERVASI BMKG DI KOTA DENPASAR - Suwignyo Prasetyo; Nany Nuraini (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
The calculation and analysis of changes in surface air temperature and rainfall in Denpasar City has been carried out using data from observation of BMKG. Data obtained from Ngurah Rai Meteorological Station during the period of 1985-2019 and Sanglah Geophysical Station during the period of 1995-2019. The results of the annual data analysis showed that in general the air temperature in Denpasar has increased. Monthly data also shows that the average air temperature in the last five years has increased than the climatological data. The annual accumulation of rainfall showed a downward trend. The monthly average for the last five years shows a shift in the beginning of the rainy season which results in a longer dry season, but there is an increase of rainfall during the dry season period.